Literatura em debate : possibilidades para o desenvolvimento da capacidade argumentativa oral no 9º ano - Ribeiro, Nadja Souza (2015)
Argue, disagree with each other´s point of view and give answers to questions are argumentative actions that permeate many communicative situations. The school, established as the place of appropriation of knowledge, can serve the pedagogical practice directed to criticality and reflection; however, at elementary school, the systematic study of argumentation is a little used. In a social discursive perspective, this report aims to present the results of action research realized at CCDMA-BA School, whose purpose is to develop oral argumentation skills in the classroom from a ruled debate. Moreover, presents the pedagogic book turned for the basic education teacher. The research is based on the theories proposed by Perelman and Olbrechts-Tyteca (2005) which highlight the theoretical principles of the argumentation; Leitão (2011) and Pontecorvo, (2005) who talk about the teaching of argumentation as a process of acquisition of knowledge; Dolz, Schneuwly and Pietro (2010) who present the application of the concept of textual genres and the study of the ruled debate by means of didactic sequence; Cosson (2014b) who discusses the literary literacy practices inside and outside the school environment. We chose the application of a didactic sequence as methodology because it promotes a systematic study of oral genres; and the reading of literary texts configured in the process as a starting point for the identification of social relevance themes and for the constitution of the arguments. The research is justified by the fact of the argumentation be a cognitive and social process that promotes the construction of knowledge and introduces discursive processes in/for human language. The results show that, when are realized pedagogical practices focused on work by language skills, the students effectively learn how to express themselves as discursive subjects. Moreover, it was observed that the study of argumentation is viable in basic education and essential, since it also promotes the reflection and the construction of knowledge. The final product of the research is registered in a Pedagogical Notebook that intends to share the experience realized with other Portuguese language teachers, thus contributing to the improvement of the practices of language in school.